Connexin 43 participates in atrial electrical remodelling through colocalization with calcium channels in atrial myocytes. (4th October 2021) - Peng, De‐wei; Lai, Ying‐yu; Luo, Xue‐shan; Li, Xin; Deng, Chun‐yu; Guo, Hui‐ming; Zhao, Jun‐fei; Yang, Hui; Liu, Yang; Wang, Zhao‐yu; Xu, Yu‐wen; Kuang, Su‐juan; et al.
Abstract: Atrial fibrillation (AF) is associated with atrial conduction disturbances caused by electrical and/or structural remodelling. In the present study, we hypothesized that connexin might interact with the calcium channel through forming a protein complex and, then, participates in the pathogenesis of AF. Western blot and whole‐cell patch clamp showed that protein levels of Cav1.2 and connexin 43 (Cx43) and basal ICa, L were decreased in AF subjects compared to sinus rhythm (SR) controls. In cultured atrium‐derived myocytes (HL‐1 cells), knocking‐down of Cx43 or incubation with 30 mmol/L glycyrrhetinic acid significantly inhibited protein levels of Cav1.2 and Cav3.1 and the current density of ICa, L and ICa, T . Incubation with nifedipine or mibefradil decreased the protein level of Cx43 in HL‐1 cells. Moreover, Cx43 was colocalized with Cav1.2 and Cav3.1 in atrial myocytes. Therefore, Cx43 might regulate the ICa, L and ICa, T through colocalization with calcium channel subunits in atrial myocytes, representing a potential pathogenic mechanism in AF.